Bone density measurements from CT scans may predict the healing capacity of scaphoid waist fractures. (14th September 2020) - Miyamura, Satoshi; Lans, Jonathan; He, Janice J.; Murase, Tsuyoshi; Jupiter, Jesse B.; Chen, Neal C.
Abstract : Aims: We quantitatively compared the 3D bone density distributions on CT scans performed on scaphoid waist fractures subacutely that went on to union or nonunion, and assessed whether 2D CT evaluations correlate with 3D bone density evaluations. Methods: We constructed 3D models from 17 scaphoid waist fracture CTs performed between four to 18 weeks after fracture that did not unite (nonunion group), 17 age-matched scaphoid waist fracture CTs that healed (union group), and 17 age-matched control CTs without injury (control group). We measured the 3D bone density for the distal and proximal fragments relative to the triquetrum bone density and compared findings among the three groups. We then performed bone density measurements using 2D CT and evaluated the correlation with 3D bone densities. We identified the optimal cutoff with diagnostic values of the 2D method to predict nonunion with receiver operating characteristic (ROC) curves. Results: In the nonunion group, both the distal (100.2%) and proximal (126.6%) fragments had a significantly higher bone density compared to the union (distal: 85.7%; proximal: 108.3%) or control groups (distal: 91.6%; proximal: 109.1%) using the 3D bone density measurement, which were statistically significant for all comparisons. 2D measurements were highly correlated to 3D bone density measurements (Spearman's correlation coefficient (R) = 0.85 to 0.95). Using 2D measurements, ROC curve analysis revealed the optimal cutoffs of 90.8% and 116.3% for distal and proximal fragments. This led to a sensitivity of 1.00 if either cutoff is met and a specificity of 0.82 when both cutoffs are met. Conclusion: Using 3D modelling software, nonunions were found to exhibit bone density increases in both the distal and proximal fragments in CTs performed between four to 18 weeks after fracture during the course of treatment. 2D bone density measurements using standard CT scans correlate well with 3D models. In patients with scaphoid fractures, CT bone density measurements may be useful in predicting the likelihood of nonunion. Cite this article: Bone Joint J 2020;102-B(9):1200–1209.